2010
DOI: 10.1007/s00127-010-0314-z
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of acute mental health care in an ethnically diverse inner city: qualitative interview study

Abstract: Home treatment was popular but hard to deliver in deprived surroundings and placed a strain on carers. Interventions to enhance community treatments in deprived areas are needed, along with remedial interventions to improve therapeutic relationships in hospital settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(53 citation statements)
references
References 26 publications
3
50
0
Order By: Relevance
“…11 16 Although Weich et al showed no evidence of service users' perceived ethnicity as a major influence on their experience of acute care, our and other studies have shown that service users can be acutely aware of the 'whiteness' of institutions and perceive mental health services to reinforce a White Euro-centric model of healthcare with little consideration or understanding of ethnicity. 24 The prominent role of social networks identified in our study was consistent with previous research, 23 24 in particular the preference of family and friends as a source of help for common mental health problems, rather than healthcare professionals. Participants recognised social networks as a source of support, enabling discussion of problems and access to services.…”
Section: Discussionsupporting
confidence: 90%
“…11 16 Although Weich et al showed no evidence of service users' perceived ethnicity as a major influence on their experience of acute care, our and other studies have shown that service users can be acutely aware of the 'whiteness' of institutions and perceive mental health services to reinforce a White Euro-centric model of healthcare with little consideration or understanding of ethnicity. 24 The prominent role of social networks identified in our study was consistent with previous research, 23 24 in particular the preference of family and friends as a source of help for common mental health problems, rather than healthcare professionals. Participants recognised social networks as a source of support, enabling discussion of problems and access to services.…”
Section: Discussionsupporting
confidence: 90%
“…Most notably, many service users are dissatisfied, describing wards as non-therapeutic and frightening [3], [4], [5]. Poor relationships between staff and service users are frequently reported [6], [7], [8]. Inpatient ward staff identify several barriers to developing therapeutic relationships including: low staffing levels; an associated lack of staff continuity; bureaucratic demands; and uncertainty about the adoption and implementation of therapeutic models [9].…”
Section: Introductionmentioning
confidence: 99%
“…They also are in keeping with findings of significant variations between places, 9 20 with the largest increase in the South East of England. Despite the great success and popularity of home treatment for acute mental health crises, 10 it is clear that these services are hard to provide in places with high levels of socioeconomic deprivation and where family and other sources of community support are difficult to secure and sustain. These are also the areas with the largest ethnic minority populations and where services are most likely to be perceived as coercive and unsatisfactory.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…[4][5][6][7] This increase in the use of compulsory detention sits uneasily with patients and professionals equally. [8][9][10][11][12] It is also a source of concern to service commissioners and service providers, given the high costs of inpatient care. The increasing rate of involuntary treatment represents a major financial obstacle to further investment in community services, particularly at times of austerity.…”
Section: Introductionmentioning
confidence: 99%